2019
DOI: 10.1101/686915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Independent evolution of polymerization in the Actin ATPase clan regulates hexokinase activity

Abstract: Yeast glucokinase activity is limited by its polymerization, which is critical for cell viability during glucose refeeding. AbstractThe actin protein fold is found in cytoskeletal polymers, chaperones, and various metabolic enzymes. Many actin-fold proteins, like the carbohydrate kinases, do not polymerize. We find that Glk1, a Saccharomyces cerevisiae glucokinase, forms two-stranded filaments with unique ultrastructure, distinct from that of cytoskeletal polymers. In cells, Glk1 polymerizes upon sugar additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Most of these metabolic filaments are assembled from important regulatory enzymes, which suggests polymerization may play a role in modulating flux through these pathways. Recently, in just a few cases, structural and biochemical studies have provided insight into the functional consequences of enzyme filament assembly, suggesting that one role of polymers is to regulate activity by locking enzymes into active or inactive conformations through assembly contacts (Hunkeler et al 2018; Barry et al 2014; Lynch et al 2017; Webb et al 2018; Stoddard et al 2019). Thus, it was surprising when our initial characterization of IMPDH2 filaments showed that assembly did not affect enzymatic activity or the ability to switch between active or inactive conformations (Anthony et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these metabolic filaments are assembled from important regulatory enzymes, which suggests polymerization may play a role in modulating flux through these pathways. Recently, in just a few cases, structural and biochemical studies have provided insight into the functional consequences of enzyme filament assembly, suggesting that one role of polymers is to regulate activity by locking enzymes into active or inactive conformations through assembly contacts (Hunkeler et al 2018; Barry et al 2014; Lynch et al 2017; Webb et al 2018; Stoddard et al 2019). Thus, it was surprising when our initial characterization of IMPDH2 filaments showed that assembly did not affect enzymatic activity or the ability to switch between active or inactive conformations (Anthony et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme is induced in the absence of glucose and expressed in high glucose (Maitra 1970). A fusion protein of Glk1 and GFP is found to be diffused throughout the cytoplasm in the absence of glucose, but formed fiber-like self-assemblies in the presence of glucose (Stoddard et al 2019). These bundles rapidly disassemble when glucose was removed from the growth media (Stoddard et al 2019).…”
Section: Structurally Characterized Enzyme Filamentsmentioning
confidence: 99%
“…A fusion protein of Glk1 and GFP is found to be diffused throughout the cytoplasm in the absence of glucose, but formed fiber-like self-assemblies in the presence of glucose (Stoddard et al 2019). These bundles rapidly disassemble when glucose was removed from the growth media (Stoddard et al 2019). Purified Glk1 at 7.5 μM is non-filamentous in the absence of ligands, but was found to form helical filaments in vitro in the presence of its substrates (ATP and glucose, mannose, glucosamine) or products (ADP and sugar-6-phosphate) (Stoddard et al 2019).…”
Section: Structurally Characterized Enzyme Filamentsmentioning
confidence: 99%
See 2 more Smart Citations